Asuhan Keperawatan Pada An. A Dengan Vomitus Di Ruang Anggrek 1 RSUD dr. Soeselo Kabupaten Tegal - Risma Septiani; Esti Nur Janah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Vomitus is the forceful expulsion of gastric contents through the mouth, commonly occurring in children as a clinical manifestation of gastrointestinal diseases. Based on medical records of RSUD dr. Soeselo, Tegal Regency, vomitus cases increased to 355 cases in 2025. Therefore, comprehensive nursing care is needed to address problems arising from vomiting in children. This study used a descriptive method in the form of a case study through a nursing process approach, aimed at describing nursing care for a pediatric patient with vomitus. Three nursing diagnoses were identified in An. A with vomitus: Nausea related to gastric irritation/stimulation of the vomiting center, Risk of Fluid Imbalance related to repeated vomiting, and Knowledge Deficit related to lack of information exposure. Nursing interventions provided included Vomiting Management, Fluid Management, and Health Education. After three days of nursing implementation, all three nursing diagnoses were resolved, marked by the disappearance of nausea, improved appetite, normal hydration status (moist mucosa, good skin turgor, pulse 88x/minute), and the patient's mother and patient being able to understand and re-explain health education material about vomitus.